A physico-chemical approach to the study of the binding interaction between S-adenosyl- l-methionine and polyanions: binding constants and nature of the interaction with sodium poly(styrene sulfonate) - Barbato, Gaetano; Calabria, Rita; Cartení-Farina, Maria; D'Auria, Gabriella; De Rosa, Mario; Sartorio, Roberto; Warzburger, Silvana; Zappia, Vincenzo (Biochimica et biophysica acta, 1989)
The interaction between S-adenosyl- l-methionine (AdoMet) and sodium poly(styrene sulfonate) (NaPSS) was studied by means of ultrafiltration and ultraviolet absorption spectroscopy at several pH values and sodium sulfate concentrations. The results obtained are interpreted mainly in terms of electrostatic interactions and permit the evaluation of the binding constants under different experimental conditions. Furthermore, ultraviolet absorption spectroscopy data show a specific short-range interaction between the aromatic electronic system of AdoMet and the NaPSS aromatic ring. The results indicate that the binding strength is greatly affected by the AdoMet positive charge on the adenine ring. The other positive charges on both the sulfonic pole and the amino acidic group of AdoMet contribute only weakly to the binding to the polyanionic matrix, thus assuring some stability of AdoMet even at physiological pH.